Consumer Social Responsibility - Bettina Rockenbach; Mark Pigors (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate the emergence of socially responsible (SR) production through consumer decisions. Our experimental treatments vary market competitiveness and consumers information on social responsibility in production. We show that irrespective of consumers information SR production reduces monopolistic supplier s profit and is therefore unlikely to emerge. With supplier competition, SR production positively influences consumers buying decisions and suppliers offering SR products achieve significantly higher profits, as long their price is not too high. Our results yield valuable insights into the possibilities and limitations of promoting SR production through consumer behavior, and provide evidence for positive effects of competition on moral behavior.
Keywords: M14; C91; A13; 330